Prospect of Development of Patchouli Oil Processing In IKM XYZ in Buke village District Buke South Konawe Regency - sakir, Sakir; Rianda, La; Purnomo, Heri (Jurusan Ilmu dan Teknologi Pangan, Fakultas Pertanian,, 2020)
This study aims to determine the prospects for the development of patchouli processing business XYZ in Buke village,Â Buke District, South Konawe Regency by looking at the financial feasibility analysis. The financial feasibility used consists of Net Present Value (NPV), Benefit-Cost Ratio (B / C Ratio), R / C Ratio, Pay Back Period (PBP), and Break-Even Point (BEP). This research was conducted from July to August 2019. The data used are primary data and secondary data. Analysis of the data used in this research is quantitative descriptive. The results of the financial feasibility of the patchy processing business of IKM XYZ are Net Present Value (NPV) of Rp. 12,521,218, Benefit-Cost Ratio (B / C Ratio) of 1,0086, R / C Ratio of 1,178, Pay Back Period (PBP) of 2.63 months, and Break-Even Point (BEP) of 164.98. From the results of the calculation of the financial feasibility of the patchy processing business, IKM XYZ is declared feasible to be developed and has good prospects.